2019
DOI: 10.1371/journal.pmed.1002887
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reduced dose of ready-to-use therapeutic foods in children with uncomplicated severe acute malnutrition: A randomised non-inferiority trial in Burkina Faso

Abstract: Background Children with uncomplicated severe acute malnutrition (SAM) are treated at home with ready-to-use therapeutic foods (RUTFs). The current RUTF dose is prescribed according to the weight of the child to fulfil 100% of their nutritional needs until discharge. However, there is doubt concerning the dose, as it seems to be shared, resulting in suboptimal cost-efficiency of SAM treatment. We investigated the efficacy of a reduced RUTF dose in community-based treatment of uncomplicated SAM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
100
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(112 citation statements)
references
References 38 publications
11
100
1
Order By: Relevance
“…Most of our subjects qualified for SAM on the basis of MUAC, rather than WLZ or oedema. Our graduation rates were consistent with those from outpatient feeding programmes in Ethiopia and Burkina Faso that included large numbers of children who were enrolled using MUAC criteria 25 26. While these studies used the same criteria for SAM treatment, these populations were not equivalent in their severity of SAM.…”
Section: Discussionsupporting
confidence: 73%
“…Most of our subjects qualified for SAM on the basis of MUAC, rather than WLZ or oedema. Our graduation rates were consistent with those from outpatient feeding programmes in Ethiopia and Burkina Faso that included large numbers of children who were enrolled using MUAC criteria 25 26. While these studies used the same criteria for SAM treatment, these populations were not equivalent in their severity of SAM.…”
Section: Discussionsupporting
confidence: 73%
“…The expected consequence of this would be to treat them with a lower RUTF dose, without routine medical treatment, and with a lesser level of medical assessment and follow-up, which may affect treatment outcomes Although currently available evidence on this topic is limited, a RUTF dose meeting total daily nutritional requirements may improve recovery and prevent relapse compared to RUTF given as a supplement to the usual diet [38]. Recent studies involving uncomplicated SAM patients reported important incidence of co-morbidities and referrals to hospital during the treatment period, thereby highlighting the importance of keeping these patients under close medical attention [39,40]. Failure to adequately address co-morbidities occurring during outpatient treatment has been highlighted as important risk factors of poor treatment outcomes [41].…”
Section: Resultsmentioning
confidence: 99%
“…The expected consequence of this would be to treat them with a lower RUTF dose, without routine medical treatment, and with a lesser level of medical assessment and follow-up, which may affect treatment outcomes Although currently available evidence on this topic is limited, a RUTF dose meeting total daily nutritional requirements may improve recovery and prevent relapse compared to RUTF given as a supplement to the usual diet [38]. Recent studies involving uncomplicated SAM patients reported important incidence of co-morbidities and referrals to hospital during the treatment period, thereby highlighting the importance of keeping these patients under close medical attention [39,40]. Failure to adequately address comorbidities occurring during outpatient treatment has been highlighted as important risk factors of poor treatment outcomes [41].…”
Section: Discussionmentioning
confidence: 99%